DEVELOPMENT OF PHONETIC COMPETENCE IN CONDITIONS OF ARTIFICIAL MULTILINGUALISM - Namozova , Dilnoza Berdimurotovna (Innovative Development in Educational Activities, 2023)
The article explores the features of teaching the pronunciation part of speech in the conditions of contact of three or more languages. These conditions are referred to as artificial multilingualism. The goal of teaching phonetics in artificial multilingualism, as well as in teaching the first foreign language, is to form phonetic competence, which includes specific skills (auditory and pronunciation), knowledge and skills. Special attention is paid to the interaction of phonetic skills of contacting languages. The result of this interaction is phonetic interference.